PENGETAHUAN DENGAN SIKAP DALAM INTERVENSI KEPERAWATAN BAYI RESIKO TINGGI HIPOTERMI DI RUANGAN ICU - Andi Akifa Sudirman; Dewi Modjo (-, 2021)
This research aims to determine the correlation of knowledge and attitude of the nurse in nursing intervention toward babies with high risk hypothermia in NICU room of RSUD Tani dan Nelayan district Boalemo. Descriptive correlation is used as the method of the research with total sampling as the technique of taking samples. The data were collected through questionnaire and analyzed using chi square test. The result of frequency distribution showed that most of the nurses which is 11 nurses (73 %) have good knowledge about hypothermia and most of the respondents which is 13 people (86,67 %) have positive attitude and have already given a suitable nursing care intervention. Based on the chi-square test, there is correlation between the knowledge and attitude of the nurse in nursing intervention toward babies with high risk hypothermia in NICU room of RSUD Tani dan Nelayan district Boalemo.